Desenvolvimento da autoria nos anos iniciais do ensino fundamental em perspectiva discursiva - Custodio, Rosane Lemos Barreto (2018)
This Doctoral Thesis proposes to evaluate, from the perspective of Discourse Analysis, the written production of students in the early years of elementary school to identify possible evidence of authorship immersed in a complex process that constitutes the development of writing and the aspects to be she related. The study aimed to understand if it is possible to develop the authorship process together with the learning of writing, allowing students to assume authorial positions gaining autonomy to (illusorily) control the meaning effects of their texts by properly selecting the linguistic resources that the language offers. To this end, a period of intervention was established with students to provide them with the practice of writing as a social practice, proposing specific activities involving discursive genres. From the result of this work, we selected some texts that presented a certain singularity in its construction drawing attention to the presence of authorship. As a research science, Ginzburg's (1989) Induction Paradigm is brought in an attempt to reach clues, apparently not perceptible, in student productions, highlighting particularities of his writing that point to indications of authorship. The theoretical path was also traced with the voices of Orlandi (2012), Bakhtin (2003), Furlanetto (2008), Maingueneau (2015) and Possenti (2209), among others. The analysis indicates indications of authorship present in the students' texts, resulting in the indispensability of practicing in school the written expression that can develop the autonomy and style of an incomplete subject, as well as the language that constitutes it.